(untitled) (Biological Sciences - PJSIR, 2008)
Pakistan Journal of Scientific and Industrial Research (PJSIR) completed its fifty years of uninterrupted publication in the year 2007; it started its publication in 1958 as a quarterly. Before going further into the subject matter under review, it seems appropriate to reproduce here ‘The Foreword’ that appeared in the first issue of the Journal. This Foreword was written by Prof. Dr. Salimuzzaman Siddiqui, the founder Chairman of the Pakistan Council of Scientific and Industrial Research (PCSIR); it describes not only the importance of scientific research in the industrial development of the country but also provides a broad scenario that prevailed in the country at that time and how steps were taken to build up the infrastructure that is necessary for scientific and industrial research. The need for bringing out the Journal of Scientific and Industrial Research is described in the said ‘Foreword’ alongwith the desire to develop this Journal into a monthly publication ‘as early as possible’.